Quality assessment of raw and pasteurized milk in Gondar city, Northwest Ethiopia: A laboratory-based cross-sectional study. Issue 3 (March 2023) - Desye, Belay; Bitew, Bikes Destaw; Amare, Dagnachew Eyachew; Adane Birhan, Tsegaye; Getaneh, Alem; Gufue, Zenawi Hagos
Abstract: Milk is a complete and highly nutritious source of food for human beings. However, in many developing countries, including Ethiopia, the quality of milk products has become a major health concern for consumers, particularly for infants and children. Therefore, the aim of the present study was to assess the quality of raw and pasteurized milk marketed in Gondar city, Northwest Ethiopia. A laboratory-based cross-sectional study was conducted on 90 milk samples. The samples were chosen using a simple random sampling technique. For statistical analysis, ANOVA and the Pearson correlation coefficient were used. The specific gravity of pasteurized milk, farm milk, and milk vendors were found to be 1.021, 1.027, and 1.026, respectively. Farm milk, milk vendors, and pasteurized milk had fat contents of 3.38%, 3.22%, and 3.09%, respectively. The total bacterial count in pasteurized milk, farm milk, and milk vendors was found to be 7.08, 6.73, and 6.94 log10 CFU/mL, respectively. In raw milk, hydrogen peroxide (7.7%), formalin (7.7%), and water (3.8%) were found, whereas in pasteurized milk, hydrogen peroxide (50%), formalin (50%), and water (19.8%) were found. Based on the findings of this study, the quality of both raw and pasteurized milk was found to be poor as per the milk quality standards. This may cause significant public health-related problems. Therefore, an appropriate intervention should be conducted to improve the quality of milk.